Safety Management of Ultra-high Voltage Substation Equipment Operation - Liu, Jinghui; Zhu, Guangze; Xia, Tuo; Xu, Zhen (International Journal of Mechanical and Electrical Engineering, 2024)
Ultra-high voltage substation plays an important role in the modern power system. It is the transmission hub of power, connecting large power plants and end users. With the continuous expansion of power grid scale and the improvement of voltage level, the safety management of ultra-high voltage substation equipment operation is particularly important. Based from the characteristics of ultra-high voltage substation, this paper will systematically study and discuss the key links of equipment operation safety management, in order to provide useful reference for improving the safe and stable operation level of China's power system.